Nanomolecular Materials: For New Generation Sensor Technologies (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Nanomolecular materials have gained significant importance in many areas of science and technology in recent years, in particular in sensor technologies. These materials are characterized by their unique physicochemical properties, which allow them to be used in the production of sensors requiring high sensitivity and accuracy. Nanomolecular materials are mainly nanometer-sized structures, which are very large in relation to their surface area. These properties also allow them to change their chemical reactivity and physical properties.